Mechanism of HMGB1–RAGE in Kawasaki disease with coronary artery injury - Biying Qian; Hua Huang; Mingye Cheng; Tingting Qin; Tao Chen; Jianmei Zhao (European Journal of Medical Research, 2020)
Abstract Background Kawasaki disease (KD) is a common, yet unknown etiology disease in Asian countries, which causes acquired heart disease in childhood. It is characterized by an inflammatory acute febrile vasculitis of medium-sized arteries, particularly the coronary arteries. High-mobility group box-1 protein (HMGB1) is a non-histone chromosomal-binding protein present in the nucleus of eukaryotic cells, which contains 215 amino acid residues. Although the cellular signal transduction mechanisms of HMGB1 are currently unclear, the important role of the receptor for advanced glycation end-products (RAGE), the main receptor for HMGB1 has been reported in detail. The purpose of our study was to verify the mechanism and clinical significance of HMGB1-RAGE in coronary artery injury of Kawasaki disease. Methods 52 blood samples of patients in KD were collected, and the coronary artery Z score was calculated according to the echocardiographic results. The Z score ≥ 2.0 was classified as coronary artery lesions (CAL); otherwise, it was no-coronary artery lesions (NCAL). In addition, the fever group and control group were set. Among them, the fever group were children with fever due to respiratory tract infection at the same time period as KD (heat peak ≥ 38.5 ℃). The normal group were children at a routine physical examination in the outpatient clinic of Nantong University and the physical examination center of the child care insurance, and there were no infectious diseases and heart diseases. The serum levels of HMGB1, RAGE, and NF-κB in each group were detected by ELISA. The animal model of KD was established using the New Zealand young rabbits. We used RT-qPCR/H&E staining/immunohistochemistry/ELISA and western blot to detect the level of HMGB1/RAGE and NF-κB. Results In this study, we found that the HMGB1/RAGE/NF-κB axis was elevated in the serum of children with KD. In addition, an animal model of KD was subsequently prepared to examine the pathological changes of the coronary arteries. We found that the serum levels of HMGB1/RAGE/NF-κB in rabbits with KD were significantly higher than those of the control group. Moreover, the lumen diameter of the coronary artery was slightly enlarged, and the wall of the tube became thinner and deformed. In addition, the HMGB1/RAGE/NF-κB levels in the coronary artery were higher in the rabbits with KD in the acute phase. Conclusions On the whole, the findings of this study demonstrate that the expression of HMGB1/RAGE/NF-κB is altered at different stages of KD, suggesting that the HMGB1/RAGE/NF-κB signaling pathway plays an important role in vascular injury in KD. The results of this study may have important implications for the early warning of coronary artery lesions in KD.